ANALISIS KESIAPAN ASOSIASI PENGOBAT TRADISIONAL TERHADAP RENCANA IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 103 TAHUN 2014 TENTANG PELAYANAN KESEHATAN TRADISIONAL DI KOTA SEMARANG - Ratna Murpratiwi; Sutopo Patria Jati; Anneke Suparwati (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2016)
The Government of the Republic of Indonesia considering to implement the provisions of Pasal 59 ayat (3) about traditional health care in Undang-Undang Nomor 36 Tahun 2009 about health, need to establish government regulation of Traditional health care, then demoted to Peraturan Pemerintah Nomor 103 Tahun 2014 about traditional health ministry to revise Keputusan Menteri Nomor 1076 tahun 2003 about traditional medicine and Peraturan Menteri Kesehatan Nomor 1109 tahun 2007 about implementation of complementary medicine Alternative , which has been issued before.After the set appeared the response from the Association of Traditional Therapist in Semarang region. This research aims to identify the readiness of the Association of Traditional Thearapist in Semarang about the implementation plan of PP Nomor 103 Tahun 2014. This research is descriptive qualitative research with in-depth interviews. The subjects of these studies amounted to 6 people as the main informant and 5 people as informant triangulation. The main informant was chosen based on the type of traditional medicine, they are herb and skills, while the informant triangulation is the Parties assessed involved in the world of traditional medicine and health care.Unreadiness of the informant described which represent the two Traditional Therapist Associations, namely in terms of understanding the different policies, the attitude tends to be refused, the characteristics of the organization that are not ready, the relationships between the organizations is quite good, as well as resources and support of social, political, economic, which is quite conducive. Both the Association of Traditional Therapist need to improve knowledge of the policy, to more open minded, improve quality, enhance the commitment of the Organization, and expanding communication with the others.